Urgensi Alquran dan Hadis Terhadap Pemikiran Filsafat Islam - Adenan Adenan; Ahmad Akbar; Abdul Rahman Ritonga; Afifatun Nisa Hasibuan; Ahmad Roihan; Arrahman Aji Prabowo (Peneliti.net, 2023)
Philosophy is a concept of thought that originated in Greece with the use of reason as a foundation. Between the Koran and philosophy is a single whole in which philosophy itself is not specifically mentioned by the Koran. For this reason, in this study, the author tries to explain some descriptions of the meaning of the Quran and Hadith, the understanding of Islamic philosophy, the position and function of the Quran and Hadith on Islamic philosophical thought. The purpose of this study is to provide some elaboration related to the importance of the Quran and Hadith as a support in forming patterns of Islamic philosophical thought. In this study, the authors used the Library Research method as a means to obtain information. Thus, valid data will be obtained related to the importance of the Quran and hadith in philosophy